Paryż w piosenkach Édith Piaf na zajęciach z języka francuskiego - Gajos, Mieczysław (Neofilolog, 2023)
Both of Édith Piaf's life and career were connected with Paris. Piaf's artistic output includes over 300 songs. What place does Paris have in those songs? What cognitive, linguistic and didactic value do Piaf's songs in which the capital of France appears bring? This article is an attempt to answer those questions. Based on the analysis of Édith Piaf's lyrics, a comparison and description of city place names (urbanonyms) associated with Paris has been made. The article contains suggestions for didactic solutions aimed at developing language and cultural competences in French classes.